Handgrip strength and hand dimensions in high-level inter-university judoists - Cortell-Tormo, J.; Prez-Turpin, J.; Lucas-Cuevas, A.; Perez-Soriano, P.; Llana Belloch, S.; Martinez-Patino, M. (Archives of Budo, 2013)
Background and Study Aim: Handgrip strength plays a major role in many sports. In Judo, a single grasp allows the judoka to attack, defend and counter-attack through different movements in a span of four to six directions. Some general and hand-specific anthropometric measurements have been positively related to handgrip strength. Therefore, the aim of this study was the influence of general and hand anthropometric parameters in handgrip strength and sport achievement. Material and Methods: Fifty four judokas aged 19-25 years participants of the Inter-University Championship of Spain 2009 took part in this study. Body height and body mass were measured and body mass index was calculated as general anthropometric parameters. Three groups of hand specific parameters were measured: finger spans, finger lengths and hand perimeters. The handgrip strength was measured by digital dynamometer in both hands. Results: The general and some hand-specific (finger lengths, hand perimeters) measurements were significantly different among the weight groups (p<0.05) and positively correlated with handgrip strength for the whole group. However, only a few measurements - IFL,MFL,P4,P5 - were positively correlated among weight groups. Poor correlations were found between hand-specific variables - TL,IFL,MFL,P4 - and sport achievement. Only P3 was highly correlated with sport achievement and together with FS1 explained 44.4% of its variance. Conclusions: The results indicate that the handgrip strength is mostly dependent on the basic (body height) and hand-specific (IFL, MFL, and P4) anthropometric parameters in judokas. Sport achievement was related to hand perimeter (P3), but its variability was weakly explained and thus hand-specific measurements may not be good predictors for judo performance